A two-wheel mobile robot platform for simulating and understanding spacecraft attitude dynamics and control - Pebrianti, Dwi; Abd Halim, Amir Ariff; Jais, Amirullah; Muhammad Nadzri, Mohamad Mukri Najmi; Samad, Rosdiyana; Bayuaji, Luhur (UNIVERSITI MALAYSIA PAHANG AL SULTAN ABDULLAH, 2025)
This study investigates the design and simulation of spacecraft attitude control using a two-wheeled robot as a model. Spacecraft attitude control is a complex system requiring precision in maintaining the orientation of a spacecraft relative to a desired reference frame. However, due to its complexity, it is challenging to understand the system dynamics directly. Thus, this research simulates spacecraft attitude control by mimicking the system behavior using a two-wheeled, Arduino-based mobile robot. The primary objective is to develop a control system that reads gyroscope data and adjusts the motor speeds to replicate spacecraft stabilization through reaction wheels. Additionally, a PID controller is implemented to control the robot wheel's speed to simulate the operation of reaction wheels. The platform and model were designed using Arduino and tested with system identification techniques. The motor's RPM and transfer function were modeled to analyze and fine-tune the PID controller, which significantly enhanced the system's performance. A Particle Swarm Optimization (PSO) method was used to determine the optimal PID parameters, improving system stability and precision in the movement. The results indicated that the system achieved stability with less than 10% steady-state error, minimal overshoot, and fast settling times, thus demonstrating effective attitude control through PID regulation. The system exhibited the ability to adjust the motor speed based on the yaw angle, thereby simulating the torque-free motion typical of spacecraft. This study demonstrates how combining theoretical modeling, simulation, and hardware implementation can simplify the understanding of spacecraft attitude control.